Low Grade Islet but Marked Exocrine Pancreas Inflammation in an Adult with Autoimmune Pre-Diabetes - Hiroshi Nomoto; Tatyana Gurlo; Madeline Rosenberger; Mark D. Girgis; Sarah Dry; Peter C. Butler (Case Reports in Endocrinology)
There is unexplained deficit in size and function of the exocrine pancreas in type 1 diabetes (T1D). We obtained pancreas from an individual with pre-T1D obtained at surgery and addressed the question, what is the relative inflammation in the exocrine and endocrine pancreas in pre-T1D in the absence of the potential confounding changes at autopsy or in brain dead organ donors. Pancreas was removed surgically from a 36 year woman for benign neuroendocrine tumors (NET). The patient had gestational diabetes at age 29 and has a 23 year old sister with T1D. Pre-operative fasting glucose of 109 mg/dl and HbA1C 5.8% revealed prediabetes with an anti-GAD 1,144 (5–250 U/ml) together with family history implying pre-T1D. There was patchy low grade immune infiltration in some, but not all, islets that met criteria for autoimmune insulitis. The exocrine pancreas showed more abundant inflammation with areas of chronic pancreatitis and acinar to ductal metaplasia, and with other areas of atrophy and fatty infiltration. In pre-T1D inflammation may be more prominent in the exocrine than the endocrine pancreas, calling into question the sequence of events and assumed islet centric basis of autoimmunity leading to T1D.